Role of Literation in Post-Disaster Recovery - Sari, Novita; Kurniati, Euis (International Conference on Elementary Education, 2020)
Indonesia is a country located in the "Pacific Ring of Fire" or Ring of Fire on Pacific Rims, Indonesia has 13% of the total volcanoes in the world. As of 2000 various natural disasters have occurred in Indonesia. Trauma counseling is a very broad field of coverage, although professionals in systematic trauma, need to recognize the impact of trauma that contributes to the institution, culture, and society. Literacy has traditionally been understood as the ability to read and write, the ability to use language that can optimize all audio, visual and audio visual abilities. The development of language skills is reading, writing, listening, speaking, seeing, presenting, and critical thinking, linguistic intelligence skills can help carry out activities in the context of post-disaster traumatic recovery. Repairing and restoring all aspects of public or community services to an adequate level in post-disaster areas is an effort in post-disaster rehabilitation and reconstruction, apart from the physical injuries suffered by many victims of the disaster, emotionally damaged